(untitled) (Indian Journal of Animal Production and Management, 2014)
The cost of production of day-old chicks was estimated in hatcheries located in an around Guwahati city of Kamrup (Metro) district in Assam. The total 17 numbers of hatcheries were selected for the study. The data were collected for a period of one year from the hatchery owners and intermediaries, using a set of structured interview schedule specially prepared for the study. The study revealed that the cost of production of day-old chicks in different hatcheries ranged from Rs.18.32 to Rs.20.08. From the overall observation it could be concluded that the highest cost of production per chick recorded was Rs.20.08 and the lowest cost of production per chick recorded was Rs. 18.32.